Postoperative Recurrence of a Mycotic Aneurysm at the Aortic Arch in a Patient Treated for a Ruptured Left Common Iliac Artery Aneurysm Due to Mycobacterium Bovis after Intravesical Bacillus Calmette-Guérin Therapy - Watanabe, Taiji; Takahashi, Akiyuki; Yamashita, Eijiro; Okawa, Kazunari; Shunto, Keisuke (Japanese Journal of Vascular Surgery, 2021)
A 68-year-old man was treated for bladder cancer with transurethral resection, followed by adjuvant Bacillus Calmette-Guérin (BCG) therapy 2 years ago. Computed tomography (CT) revealed an abnormal shadow around the left common iliac artery. As positron emission tomography-computed tomography (PET-CT) showed an abnormal uptake in the mediastinal lymph nodes and common iliac artery, among other sites, malignant lymphoma was suspected. The patient was referred to another hospital with sudden left lower abdominal pain. CT revealed impending rupture of a left common iliac artery aneurysm. He was thus transferred to our hospital. Emergency aorto-iliac reconstruction was performed with a prosthetic graft. The pathological findings of aortic wall revealed epithelioid cell granuloma, and he was diagnosed with tuberculous mycotic aneurysm. Although he received anti-tuberculosis therapy after the operation, magnetic resonance imaging four months later showed an aneurysm in the aortic arch. We diagnosed him with recurrence of tuberculous mycotic aneurysm and performed total arch replacement. The pathological findings of the resected aortic wall revealed epithelioid cell granuloma, just as at the initial operation. Tuberculous mycotic aneurysm after BCG therapy can recur even during anti-tuberculosis therapy.